Factors Affecting Biosorption of Direct Dyes from Aqueous Solution - Safa, Yusra; Nawaz Bhatti, Haq (Asian Journal of Chemistry, 2010)
Dyes contamination in ground and aquatic environment has become a serious menace today. Removal of dyes from wastewater before discharging to environment is necessary for the safety of living beings. Dyes are difficult to degrade due to complex structures. Different techniques are used to remove the dyes from wastewater. Among these techniques, biosorption has emerged as an effective and ecofriendly technique. Biosorption of dyes using different biomaterials has been investigated by different researchers. This review article gives an insight into the removal of different synthetic direct dyes using different biomaterials from aqueous solution. The effect of various process para-meters such as pH, biosorbent dose, initial dye concentration, sorbent particle size, agitation time, temperature, ionic strength etc. has been discussed.